2013
DOI: 10.1007/s00203-013-0915-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a possible respiratory arsenate reductase in Denitrovibrio acetiphilus, a member of the phylum Deferribacteres

Abstract: Denitrovibrio acetiphilus N2460(T) is one of the few members of the phylum Deferribacteres with a sequenced genome. N2460(T) was capable of growing with dimethyl sulfoxide, selenate, or arsenate provided as a terminal electron acceptor, and we identified 15 genes that could possibly encode respiratory reductases for these compounds. The protein encoded by one of these genes, YP_003504839, clustered with respiratory arsenate reductases on a phylogenetic tree. Transcription of the gene for YP_003504839, Dacet_21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…In agreement with our data, it has been described how higher levels of Tenericutes in beef calves received Se-biofortified alfalfa . Moreover, Deferribacteres phylum members, concretely Denitrovibrio acetiphilus N2460 ( T ), have been linked with the capability of growing with dimethyl sulfoxide, selenate, or arsenate provided as a terminal electron acceptor, and 15 genes have been identified that could possibly encode respiratory reductases for these compounds . In fact, Deferribacter desulfuricans has also been reported to grow at the expense of dissimilatory reduction of As­(V) to As­(III) .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with our data, it has been described how higher levels of Tenericutes in beef calves received Se-biofortified alfalfa . Moreover, Deferribacteres phylum members, concretely Denitrovibrio acetiphilus N2460 ( T ), have been linked with the capability of growing with dimethyl sulfoxide, selenate, or arsenate provided as a terminal electron acceptor, and 15 genes have been identified that could possibly encode respiratory reductases for these compounds . In fact, Deferribacter desulfuricans has also been reported to grow at the expense of dissimilatory reduction of As­(V) to As­(III) .…”
Section: Resultssupporting
confidence: 90%
“… 43 Moreover, Deferribacteres phylum members, concretely Denitrovibrio acetiphilus N2460 ( T ), have been linked with the capability of growing with dimethyl sulfoxide, selenate, or arsenate provided as a terminal electron acceptor, and 15 genes have been identified that could possibly encode respiratory reductases for these compounds. 44 In fact, Deferribacter desulfuricans has also been reported to grow at the expense of dissimilatory reduction of As(V) to As(III). 45 In addition to As(V), D. desulfurican strain MPA-C3 utilizes NO 3– , Se(VI), Se(IV), fumarate, and Fe(III) as electron acceptors and acetate, pyruvate, fructose, and benzoate as sources of carbon and energy.…”
Section: Resultsmentioning
confidence: 99%
“…However, Deferribacteres is now invalid under ICNP rule 8, as is class Chrysiogenetes with sole order Chrysiogenales of anaerobic arsenate-respiring flagellate negibacteria (Garrity and Holt 2001b). As Chrysiogenales and Deferribacterales are strongly sisters on our CAT and ML RP trees and have rather similar phenotypes (Deferribacterales subclade comprising Denitrovibrio and Seleniivibrio can also respire arsenate (Denton et al 2013;Rauschenbach et al 2013)), making both separate phyla (Chrysiogenetes, Deferribacterales: Garrity and Holt 2001a, b) was unjustified rank inflation. We therefore group both orders of metal reducers in the same new class Deferribacteria within a reestablished proteobacterial subphylum Geobacteria, which comprises Deferribacteria plus ε-proteobacteria, fairly strongly supported sisters on CAT but separated on ML RP trees (see Taxonomic Appendix).…”
Section: Proteobacteria Comprise Subphyla Rhodobacteria Acidobacteria and Geobacteriamentioning
confidence: 75%
“…A custom database of 110 amino acid sequences from the catalytic subunit of representative complex iron-sulfur molybdoenzymes (CISM, Supplementary Table S1 ) was prepared using sequences from various references ( Rothery et al , 2008 ; Schoepp-Cothenet et al , 2012 ; Denton et al , 2013 ; Grimaldi et al , 2013 ). The sequences were downloaded from NCBI and edited in Geneious ( Kearse et al , 2012 ).…”
Section: Methodsmentioning
confidence: 99%